Peningkatan Keterampilan Menulis Opini dengan Menggunakan Model Sinektik pada Siswa Kelas XI SMA Negeri 2 Barru - Fatima, Fatima; Muin, Nurmiah; Puspitasari, Andi (Innovative: Journal Of Social Science Research, 2023)
Indonesian Language and Literature Education, Faculty of Letters, Indonesian Muslim University. (Supervised by Nurmiah Muin and Andi Puspitasari. This research aims to improve student learning outcomes. Using the Synectic Model in learning can improve students' writing abilities as expected for Class XI IPA 5 SMA 2 Barru students. This type of research is Classroom Action Research (PTK). Classroom action research aims to improve the quality or solve problems in the subjects studied by observing the level of success or consequences of their actions, to then receive additional actions which are improvements to actions or adjustments to conditions and situations in order to achieve better results. The average student score was 64 and 4 people reached the KKM or 12%. In cycle I the average score of students was 75,73 and 11 people reached the KKM or 32%. The average score of students in the second cycle increased by 83,14 and reached KKM was 31 students or 92%. Based on the results of the research and discussion above, it can be concluded that Opinion Writing Skills Using the Synectic Model can improve the learning outcomes of opinion writing for XI IPA 5 students at SMA Negeri 2 Barru. From research data conducted during the pre-cycle stage to cycle 2, we noticed different results. Where each cycle pays attention to student learning outcomes.